2006
DOI: 10.2190/3qtu-6eel-hqhf-xyf0
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Barrier Courses and Persistence in Engineering

Abstract: Attrition in engineering programs continues to be an important issue for universities across the country. This study examined the connection between student performance in barrier courses and persistence in engineering. Quantitative results showed that high school academic experience, student behaviors (including study habits, work habits, coping strategies), students' perceptions about faculty behavior (including teaching styles and the "weedout" culture), the perceived culture of support in the engineering s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 3 publications
6
114
0
Order By: Relevance
“…Prior research has shown that these "barrier courses" are a key reason why students leave STEM fields (Seymour and Hewitt 1997). Further, students' perception that a course is meant to weed students out shapes their performance in said course (Suresh 2006); therefore, it seems likely that a weed-out culture might also impact students' sense of belonging in their chosen field. To be sure, not all introductory computing courses are designed to weed-out students; the computing field is making significant efforts to encourage participation from groups historically underrepresented in computing (e.g., women, URM students, and those lacking prior computing experience), which has included efforts to make introductory courses more inclusive (Alvarado et al 2012).…”
Section: Curricular Experiences In Computingmentioning
confidence: 99%
“…Prior research has shown that these "barrier courses" are a key reason why students leave STEM fields (Seymour and Hewitt 1997). Further, students' perception that a course is meant to weed students out shapes their performance in said course (Suresh 2006); therefore, it seems likely that a weed-out culture might also impact students' sense of belonging in their chosen field. To be sure, not all introductory computing courses are designed to weed-out students; the computing field is making significant efforts to encourage participation from groups historically underrepresented in computing (e.g., women, URM students, and those lacking prior computing experience), which has included efforts to make introductory courses more inclusive (Alvarado et al 2012).…”
Section: Curricular Experiences In Computingmentioning
confidence: 99%
“…Suresh (2006) 22 found that a majority of engineering majors who earned a B-minus or below in Calculus I, Calculus II, and Physics I-strategic "gatekeeper" courses-left engineering. The freshman year model identified grades in Physics I, Calculus I, and Chemistry I as the best predictors of retention.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Beanland, a prominent engineering educator, claims "the biggest factor contributing to the failure of engineering students is inadequate competence in mathematics" 2 . Suresh 3 reports that roughly 50% of engineering majors change majors or drop out in the first or second year, due in part to performance in mathematics, as reported by Felder et al 4 . Recently, Pearson and Miller 5 found that nearly onethird of students who enter an engineering program fail to complete it, and they also found that the two strongest predictors of completion of a baccalaureate in engineering were completion of a calculus course in high school and the number of college calculus courses taken.…”
Section: Can the Spacing Effect Improve The Effectiveness Of A Math Imentioning
confidence: 92%